2008
DOI: 10.1007/s00384-008-0583-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary cancers in extracolonic sites with colorectal cancer

Abstract: Gastric cancer is the most common synchronous multiple primary cancers occurring concomitantly with colorectal cancers. Careful preoperative screening is necessary for the detection of multiple primary cancers in extracolonic sites in patients with colorectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
2
13
0
2
Order By: Relevance
“…Our data showed that GC was the most frequently associated cancer in patients with CRC both synchronously and metachronously, consistent with previous reports [9,10,[15][16][17][18][19].…”
Section: Resultssupporting
confidence: 93%
“…Our data showed that GC was the most frequently associated cancer in patients with CRC both synchronously and metachronously, consistent with previous reports [9,10,[15][16][17][18][19].…”
Section: Resultssupporting
confidence: 93%
“…The reported incidence of multiple primary cancers in extracolonic sites among CRC patients range from 2.4% to 8.7%. In this regard, the the most common extracolonic site of synchronous multiple primary cancers among CRC patients is stomach (Asia) and lung/breast (Europe) [4].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the incidence of multiple primary cancers in patients with colorectal cancer was 3.0%. The most common extra-colonic site of the multiple primary cancers among colorectal cancer patients (1.6%) was the stomach [4]. …”
Section: Discussionmentioning
confidence: 99%